Impacto da tuberculose bovina nos rebanhos leiteiros do Rio Grande do Sul - Stroeher, Fernanda Hammes (2019)
Agribusiness is one of the most important sectors in the Brazilian economy, being recognized worldwide for its agricultural production, which bovine culture stands out on the world stage with the second largest herd, behind India. However, some diseases, such as bovine tuberculosis, can interfere in the production of meat and dairy products, generating economic losses to the livestock sector, mainly in dairy cattle, which has a more confined system. The objective was to evaluate the population density of the bovine herd in the state, over the years, its relationship with bovine tuberculosis and the damage that the disease causes in the properties of the state of Rio Grande do Sul. Data from the cattle herd in Rio Grande were analyzed do Sul, observing herd, milked cows and herd / cows ratio between 1974 to 2017 and bovine tuberculosis compensation data paid by FUNDESA in the periods from 2009 to 2017. The data were analyzed using statistical analysis using the SAS® statistical software, FREQ procedure and maps were formed using the Tabwim program. We can observe a higher concentration of dairy cattle and consequently bovine tuberculosis in the Northwest region of Rio Grande do Sul. Bovine tuberculosis can generate several economic, social and public health losses on dairy farms. For these reasons, programs aimed at controlling and eradicating the disease are extremely important, in addition to the indemnities and bonuses paid, which encourage the producer to carry out the tests on their properties, thus seeking to ensure the health of their herd and a better quality product for the consumer.